2005
DOI: 10.1590/s1516-89132005000800020
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical evaluation of Rosmarinus officinalis L. essential oils

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 7 publications
6
36
1
6
Order By: Relevance
“…The mean values for the refractive index of the rosemary oil extracted by HD and MAHD were found to be the same as 1.465± 0.0005. Both specific gravity and refractive index values were found to be in good agreement with the ones for the essential oil of R. officinalis L. in literature (Atti-Santos et al 2005).…”
Section: Specific Gravity and Refractive Index Of Essential Oilssupporting
confidence: 81%
See 2 more Smart Citations
“…The mean values for the refractive index of the rosemary oil extracted by HD and MAHD were found to be the same as 1.465± 0.0005. Both specific gravity and refractive index values were found to be in good agreement with the ones for the essential oil of R. officinalis L. in literature (Atti-Santos et al 2005).…”
Section: Specific Gravity and Refractive Index Of Essential Oilssupporting
confidence: 81%
“…Rosmarinus officinalis L. (Lamiaceae), which is a small evergreen shrub (Atti-Santos et al 2005), is used in cosmetics, in traditional medicine and for flavoring food (Ramírez et al 2006). The highest quality essential oil of R. officinalis L. is obtained from the leaves (Lo Presti et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some identified constituents in this species have been also reported in A. conyzoides (Okunade, 2002;Nébié et al 2004), Chamomilla recutita (Presibella et al, 2006) and Rosmarinus officinalis (Atti-Santos et al, 2005). Results observed in this study showed this to be the first report describing the antinociceptive and anti-inflammatory activities from A. fastigiatum.…”
Section: Discussionsupporting
confidence: 73%
“…The physicochemical analysis is performed according to the procedure described by Atti-Santos et al [27] by using five parameters: specific gravity (SG), optical rotation (OR), refractive index (RI), solubility in ethanol (SE), and residue on evaporation (RE). Different results were reported by [28,29] who mentioned that GC-MS analysis of most leaves EO samples originating from India revealed α-pinene (15.01-51.82%) as the major component [30].…”
Section: Resultsmentioning
confidence: 99%